Pravastatin: An Antithrombotic Effect Independent of the Cholesterol-lowering Effect - Dangas, George; Smith, Donald A.; Unger, Allen H.; Shao, John H.; Meraj, Perwaiz; Fier, Carl; Cohen, Adam M.; Fallon, John T.; Badimon, Juan J.; Ambrose, John A. (Thrombosis and Haemostasis, 2000)
Lipid-lowering with statins reduces blood thrombogenicity. However, it is unknown whether this is purely due to LDL-cholesterol reduction, or it is related to a statin or agent specific effect. We investigated the relationship between reduction in blood thrombogenicity and the magnitude of low-density lipoprotein cholesterol (LDL-C) during pravastatin therapy.We prospectively followed for 6 months 57 hyperlipidemic patients who initiated therapy with pravastatin, and 36 patients who were randomized into placebo plus diet. Pravastatin-treated patients were grouped according to the LDL-C reduction at 6 months; (i) “adequate LDL-C reduction”: LDL-C reduction >30% from baseline or LDL-C<125 mg/dl (n = 38; LDL-C reduction 74 ± 4 mg/dl; 6-month LDL-C 119 ± 5 mg/dl); (ii) “inadequate LDL-C reduction”: neither of the above criteria (n = 19; LDL-C reduction 31 ± 5 mg/dl; 6-month LDL-C 158 ± 6 mg/dl). Placebo patients were divided into those “with LDL-C reduction” (n = 17, mean reduction 21 ± 5 mg/dl) and those “without LDL reduction” (n = 19).The following parameters were altered at 6 months in both patients with “adequate” and “inadequate” LDL-C reduction: (1) tissue plasminogen activator decreased by 1.4 ± 0.4 and 1.5 ± 0.5 ng/ml respectively (p = NS); (2) plasminogen activator inhibitor-1 decreased by 8.7 ± 2.0 and 10.1 ± 2.7 ng/ml respectively (p = NS); (3) thrombus formation under dynamic flow conditions decreased by 3.5 ± 0.9 and 2.8 ± 1.2 µm2 × 103 respectively (p = NS). In contrast, no significant changes from baseline were noted in placebo-treated patients, regardless of their LDL-C reduction category, and multivariate analysis eliminated LDL-C reduction as an independent predictor of reduction in thrombogenicity.Therefore, the reduction in thrombogenicity was not proportional to the magnitude of LDL-C reduction suggesting that a class or agent specific property is primarily responsible for the pro-fibrinolytic/antithrombotic effects observed.
Keywords: Lipids; platelet; endothelium; thrombus